2023
DOI: 10.1021/acsphotonics.2c01959
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen-Inspired ZnO/PEG Composites for Flexible Ultraviolet Photodetectors with a Giant On–Off Ratio

Abstract: Zinc oxide (ZnO) nanomaterials have attracted much attention in UV photodetectors owing to the suitable band gap and high photoelectric conversion efficiency. However, the loose structure of nanomaterials assembled by a low-temperature process cannot meet the mechanical requirements of flexible photodetectors. The high dark current caused by defects in ZnO severely drags down the response performance of photodetectors. To address these issues, we have proposed a novel strategy for constructing flexible photode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…The inclusion of poly­(ethylene glycol) (PEG), which was inspired by sunscreen, improved the interaction of ZnO nanoparticles and increased the composites’ capacity to form films and their mechanical toughness. A flexible PD created by coating standard printer paper with the ZnO/PEG combination exhibits a considerable reduction in the dark current, which results in a high responsivity of 1.77 A/W and a large specific detectivity of 3.89 × 10 13 Jones . Graphene QD-decorated ZnO (ZnO:GQD) studied by Tran et al showed less surface roughness, reduced nanoparticle size, higher photogenerated carrier transport, and extended carrier lifetime.…”
Section: Nanostructured Zno-based Uv Pdsmentioning
confidence: 99%
“…The inclusion of poly­(ethylene glycol) (PEG), which was inspired by sunscreen, improved the interaction of ZnO nanoparticles and increased the composites’ capacity to form films and their mechanical toughness. A flexible PD created by coating standard printer paper with the ZnO/PEG combination exhibits a considerable reduction in the dark current, which results in a high responsivity of 1.77 A/W and a large specific detectivity of 3.89 × 10 13 Jones . Graphene QD-decorated ZnO (ZnO:GQD) studied by Tran et al showed less surface roughness, reduced nanoparticle size, higher photogenerated carrier transport, and extended carrier lifetime.…”
Section: Nanostructured Zno-based Uv Pdsmentioning
confidence: 99%
“…The facile fabrication methods from soluble, low-temperature processable properties of the NPs also improve the device’s flexibility and stretchability. Thus, the NPs integrated with flexible substrates enable the implementation of the flexible/stretchable PDs based on ZnO NPs, Ag NPs, PbS QDs, CdSe QDs, Ag 2 Se NPs, and PbSe QDs, HgTe QDs . This section will present 0D nanomaterial-based inorganic, flexible/stretchable PDs.…”
Section: Materials For Flexible and Stretchable Pdsmentioning
confidence: 99%
“…ZnO is recognized as a wide bandgap semiconductor, featuring a bandgap of 3.3 eV, notable for its high carrier mobility and significant ultraviolet (UV) absorption coefficient, making it extensively employed in UV PDs. 26,27 It is also important to highlight that the electron affinity of ZnO is 4.2 eV, presenting a minor band shift relative to SrTiO 3 , which has an electron affinity of 4.0 eV. 28 Consequently, ZnO serves as an optimal partner for fabricating SrTiO 3 heterojunctions.…”
Section: Introductionmentioning
confidence: 99%